Advanced Manufacturing Technology: The Perceived Impact on Producer’s Value - Abdullah, Rohani; Hassan, Mohamad Ghozali (The Asian Journal of Technology Management (AJTM), 2012)
The purpose of this study is to determine which AMT has the greatest perceived impact on producer’s value and to identify which AMTs has been most successfully employed. The study population consists of senior manufacturing executives in electrical and electronic firms located in the northern region of Malaysia. The study addresses the senior manufacturing executives’ perceptions on how well specific AMTs have achieved the expectation of the firms implementing them. They are selected as respondents because of their understanding of the technology and their effects, and because as top manufacturing decision makers, their opinions are likely to shape the future technology of the organization. This study found that the type of AMT that perceived the greatest impact on producer’s value is Flexible Manufacturing System, due to its high effects on two dimensions of producer’s value: quality and cost while Just-in-Time is found to be the most successfully employed AMT among respondents. The findings of this study are significant as they contribute to the AMT literature especially in the context of Electrical and Electronic firms. Keywords: advanced manufacturing technology, producer’s value